Volatile Compounds and Off-odors Analysis of PLA from Recycling Cycle for Biodegradable Packaging Applications: An Essential Factor for Ensuring Food Safety and Quality - Paiva, Robert; Wrona, Magdalena; Nerín, Crisitina; Luminita, Georgiana; Andrea Cruz, Sandra (Jornada de Jóvenes Investigadores del I3A, 2023)
Recent European guidelines support the use of recycled and biodegradable packaging for food applications that involve single-use materials. In this work, PLA pellets were submitted to post-consumer recycling cycle industry. HS-SPME-GC-MS and HS-SPME-GC-O-MS methods have been used to detect hazardous volatile compounds and off-ofors profiles.